Impact of host stress on the replication rate of Plasmodium: take it easy to avoid malaria recurrences - Pigeault, Romain; Ruiz De Paz, Angela; Baur, Molly; Isaïa, Julie; Glaizot, Olivier; Christe, Philippe (Frontiers in Ecology and Evolution, 2023)
Malaria is widespread throughout the world and affects many animal species. Although the origin of this vector-borne disease was discovered more than a century ago, several aspects of the within-host infection dynamic are still poorly understood. Among them, the factors triggering parasite recurrences -episodes of brief increase in parasite number following a period when the parasite was either absent or present at very low levels in the blood -have still not been clearly identified. Yet, recurrences may contribute significantly to overall infection prevalence in vertebrate host populations. Here, we investigated whether artificial or natural increases in stress hormone levels in chronically infected birds influence the replication rate of Plasmodium relictum and transmission to its natural vector, the mosquito Culex pipiens. Our results provide evidence that increased levels of corticosterone, either induced by oral ingestion or caused by handling stress, can trigger malaria recurrences. However, we did not observe any effect on the transmission rate of the parasite to the mosquito vector. Our study is a first fundamental step in understanding the mechanisms underlying malaria recurrences. It remains to be ascertained whether this feature extends to other malaria system and in particular to human malaria.